Short communicationsTranscatheter closure of sinus of Valsalva aneurysm rupture in a young patient - SatIlmI, Seçkin; Bozbeyoglu, Emrah; Erta, Gökhan; YIldIrImtürk, Özlem; YIldIrIm, AydIn (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2013)
Sinus of Valsalva aneurysm rupture is a rare cardiac anomaly and demands prompt treatment. We present a case of a young patient who underwent transcatheter closure due to a ruptured sinus of Valsalva aneurysm.